Rotational Angiography Based Three‐Dimensional Left Atrial Reconstruction: A New Approach for Transseptal Puncture. Issue 1 (February 2016) - Koektuerk, Buelent; Yorgun, Hikmet; Koektuerk, Oezlem; Turan, Cem H.; Gorr, Eduard; Horlitz, Marc; Turan, Ramazan G.
Summary: Aim: Rotational angiography is a well‐known method for the three‐dimensional (3‐D) reconstruction of left atrium and pulmonary veins during left‐sided atrial arrhythmia ablation procedures. In our study, we aimed to review our experience in transseptal puncture (TSP) using 3‐D rotational angiography. Methods: We included a total of 271 patients who underwent atrial fibrillation ablation using cryoballoon. Rotational angiography was performed to get the three‐dimensional left atrial and pulmonary vein reconstructions using cardiac C‐arm computed tomography. The image reconstruction was made using the DynaCT Cardiac software (Siemens, Erlangen, Germany). Results: The mean age of the study population was 61 ± 10 years. The indications for left atrial arrhythmia ablation were paroxysmal AF in 140 patients (52%) and persistent AF patients in 131 (48%) patients. The success rate of TSP using only rotational guidance was (264/271 patients, 97.4%). In the remaining seven patients, transesophageal guidance was used after the initial attempt due to thick interatrial septum in five patients and difficult TSP due to abnormal anatomy and mild pericardial effusion in the remaining two patients. Mean fluoroscopy dosage of the rotational angiography was 4896.4 ± 825.3  μ Gym 2 . The mean time beginning from femoral vein puncture to TSP was 12.3 ± 5.5 min. Conclusion: TSP guided by rotational angiography is a safe and effective method. Our results indicate that integration of rotational angiographic images into the real‐time fluoroscopy can guide the TSP during the procedure.